2012
DOI: 10.1016/j.neulet.2012.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microglial activation within the hindbrain, nodose ganglia, and the spinal cord following subdiaphragmatic vagotomy

Abstract: Damage to peripheral nerve branches triggers activation of microglia in CNS areas containing motor neuron soma and primary afferent terminals of the damaged fibers. Furthermore, microglial activation occurs in areas containing the soma and terminals of spared nerve branches of a damaged nerve. Because the abdominal viscera are innervated by spinal afferents as well as vagal afferents and efferents, we speculated that spinal nerves might respond like spared nerve branches following damage to vagal fibers. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…Interestingly, our previous studies revealed that damage to peripheral axons of the vagus (subdiaphragmatic vagotomy) also induced transient decrease in the density of vagal afferents projecting to the NTS (Ballsmider et al 2015, Peters et al 2013) followed by vagal inputs sprouting. Vagal damage also resulted in microglia activation in the NTS and DMV (Gallaher et al 2012). We previously found that vagal afferent remodeling led to alterations in frequency and amplitude of glutamate release in the NTS (Peters et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, our previous studies revealed that damage to peripheral axons of the vagus (subdiaphragmatic vagotomy) also induced transient decrease in the density of vagal afferents projecting to the NTS (Ballsmider et al 2015, Peters et al 2013) followed by vagal inputs sprouting. Vagal damage also resulted in microglia activation in the NTS and DMV (Gallaher et al 2012). We previously found that vagal afferent remodeling led to alterations in frequency and amplitude of glutamate release in the NTS (Peters et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted the above study minocycline was administered directly into the spinal cord at a dose of 10, 50 or 100 μg/kg. Direct anti-inflammatory effects of minocycline have been reported for doses ranging from 20 to 100 mg/kg (Amin et al 2015, Gallaher et al 2012, Kumar and Addepalli 2011). Minocycline may alleviate inflammation via a decrease in bacteria-driven cytokine production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiology also revealed transient decreases in spontaneous glutamate release, and the number of primary afferent inputs [52]. Other changes in the CNS induced by vagotomy, such as microglial activation within the hindbrain, nodose ganglia, and the spinal cord have also been described [53]. However, to our knowledge, no data about the potential role of subdiaphragmatic vagotomy on LTP has been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…After blocking in 10% normal horse serum in Tris-phosphate buffered saline (TPBS, pH 7.4) sections were incubated overnight with a primary antibody against ionized calcium binding adaptor molecule 1 (Iba1) followed by an Alexa-488 secondary antibody (Invitrogen, CA) to visualize microglia activation as previously described [20]. The hindbrain sections were incubated with isolectin B4 biotin-conjugated (IB4) for 12 h at room temperature to visualize primary unmyelinated vagal afferents innervating the GI tract as previously described [21], followed by ExtrAvidin-CY3 (1:600, E-4142, Sigma-Aldrich) for 2 h. Negative controls were performed by omission of primary antibodies.…”
Section: Methodsmentioning
confidence: 99%